STUDY ON TALENT MANAGEMENT PRACTICES IN PHARMA SECTOR WITH FOCUS ON "EMPLOYEE RETENTION” (Journal of Pharmaceutical Negative Results, 2022)
The pharmaceutical sector in India currently holds a dominant position in the market for generic pharmaceuticals around the world. The industry is characterized by a one-of-a-kind mixture of both opportunities and limitations. It has achieved the global excellence standards in the mass manufacture of high-quality branded generics, which was driven by its capabilities in formulations that are of world-class standard. This achievement was driven by the fact that it has attained the mass manufacturing of branded generics. These are the result of prolonged expenditures in infrastructure and research & development on the part of industry leaders, who were also responsible for their creation. In addition, there are a huge number of small and medium-sized firms, which contributes to the industry's highly fragmented nature. The purpose of this study are to investigate the factors that contribute to employee turnover in the Indian context generally and in the pharmaceutical industry and to outline a deeper understanding of the strategies that are used for talent management and employee retention in the pharmaceutical industry.The pharmaceutical industry in India has the greatest employee turnover rate, and each industrial unit within the sector uses a unique combination of criteria and procedures to choose its talent, deliver its training, and take its various capacity-building steps. There is also a significant financial reward connected with work performance in the form of salaries and other benefits. Even with all of the necessary efforts, the retention of highly skilled employees to grass root functionaries continues to be a repeated pattern; nevertheless, the causes and impact of this phenomenon are not disclosed to aid the companies. As a consequence of this, the collecting of primary material became obligatory in order to investigate the subject in depth and evaluate the impact of the attrition problem. The secondary sources of information that were utilised in the research study have been appropriately acknowledged, and the primary data that the research scholar gathered, organized, and assessed on their own have been appropriately analyzed. The pharmaceutical sector relies on an extensive network of medical representatives, each of whom is individually tasked with driving sales of their company's wares in the marketplace. The grass-roots functionaries encompass a vast number of individuals in this category. The suggestions for lowering the rate of employee turnover are, for the most part, based on the field response from the respondents as well as management from the firms. The study was conducted in Chennai city during the month of January 2022. The primary data was collected using Google forms.